Exacerbation of N-nitrosodiethylamine Induced Hepatotoxicity and DNA Damage in Mice Exposed to Chronic Unpredictable Stress - Nayeem Bilal; Nida Suhail; Nida Suhail; Shirin Hasan; Shirin Hasan; Ghulam M. Ashraf; Sabiha Fatima; Husain Y. Khan; Mariam S. Alharbi; Athanasios Alexiou; Naheed Banu; Naheed Banu (Frontiers Media S.A., 2017)
Psychological stress contributes to increased susceptibility to a number of diseases including cancer. The present study was designed to assess the effect of chronic unpredictable stress on N-nitrosodiethylamine induced liver toxicity in terms of in vivo antioxidant status and DNA damage in Swiss albino mice. The animals used in this study were randomized into different groups based on the treatment with N-nitrosodiethylamine or chronic unpredictable stress alone and post-stress administration of N-nitrosodiethylamine. The mice were sacrificed after 12 weeks of treatment, and the status of major enzymatic and non-enzymatic antioxidants, liver function markers, lipid peroxidation and the extent of DNA damage were determined in circulation and liver tissues of all the groups. The N-nitrosodiethylamine treated group showed significantly compromised levels of the antioxidant enzymes, lipid peroxidation, and the liver function markers with enhanced DNA damage as compared to chronic unpredictable stress or control groups. A similar but less typical pattern observed in the chronic unpredictable stress treated mice. All the measured biochemical parameters were significantly altered in the group treated with the combination of chronic unpredictable stress and N-nitrosodiethylamine when compared to controls, or chronic unpredictable stress alone and/or N-nitrosodiethylamine alone treated groups. Thus, exposure to continuous, unpredictable stress conditions even in general life may significantly enhance the hepatotoxic potential of N-nitrosodiethylamine through an increase in the oxidative stress and DNA damage.